Level Of Nadzir Understanding About The Importance Of Supervision On Wakaf Management Institutions In Batam City, Indonesia - Sofiandi Sofiandi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
This research was conducted with the aim of analyzing problems related to efforts to enforce accountability on waqf management institutions in Batam City with quantitative descriptive methodology. The results of the data analysis showed that the level of understanding of nadzir on the importance of supervision to be carried out on waqf management institutions is at the medium level, which means it still has to be upgraded. This is evidenced by the fact that, in the city of Batam, none of the waqf management institutions has ever been supervised or audited. Many things must be done to overcome this problem, such as transparent and open reports, not only to the government and waqif but also to the public openly. Then, bookkeeping training, as well as the application of clear and strict rules regarding Nadzir's rights and obligations. It is hoped that accountability can be expected to emerge from the professionalism of managing waqf assets.